Resistance And Adaptation: Examining Local Responses To Colonial Governance In Garo Hills (Journal of Namibian Studies : History Politics Culture, 2023)
This research looks deep into the complex ways in which the Garo Hills people responded to colonial rule, illuminating stories of resistance and adaptability from that time period. This study sheds light on the sophisticated tactics used by the Garo by analyzing archival documents, oral histories, and anthropological data. The study adds to the larger understanding of how local inhabitants actively created their fates within the complex dynamics of colonial control by reframing resistance as more than opposition but as a dynamic form of agency. The findings underscore the resilience and adaptability of the Garo community in handling the challenges imposed by external forces.